Efektivitas Perceived Ease of Use, Perceived Value, dan Brand Credibility dalam Menciptakan User Experience dan Purchase Intention di Aplikasi Investasi - Bryant Hans Channing Panjaitan; Usep Suhud; Meta Bara Berutu (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The primary objective of this study is to analyze the effectiveness of perceived ease of use, perceived value, and brand credibility in creating user experience and purchase intention in investment applications. Data collection was conducted through questionnaires distributed online via social media platforms such as WhatsApp and Instagram. The research subjects consist of respondents who are users or potential users of the Bibit investment application, domiciled in DKI Jakarta, and aged between 18–35 years. The sample size used was 290 respondents. For the analysis process, this study utilized SPSS version 26 and Structural Equation Modeling (SEM) using AMOS version 29 for validation and data processing. Validity and reliability tests were conducted using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Subsequently, hypothesis testing was carried out on the verified variables to identify relationships between them. The findings from the analysis indicate that perceived ease of use has a significant influence on perceived value, user experience, and purchase intention. Furthermore, brand credibility was found to have a direct influence on perceived value but no direct influence on purchase intention. Meanwhile, perceived value influences user experience but does not have a direct effect on purchase intention. These findings make an important contribution to the development of academic studies related to user behavior toward digital investment applications and offer practical recommendations for system developers to enhance the overall quality of user experience in digital investment applications.